Preparation, characterization, drug release and computational modelling studies of antibiotics loaded amorphous chitin nanoparticles. (1st December 2017) - Gayathri, N.K.; Aparna, V.; Maya, S.; Biswas, Raja; Jayakumar, R.; Mohan, C. Gopi
Highlights: Antibiotics loaded amorphous chitin nanoparticles (AC-NPs) was prepared. Hydrophobic drug showed as best carrier for AC-NPs. Computational binding energy (BE) between AC-NPs and antibiotics were studied. BEs correlates well with experimental drug loading and entrapment efficiencies. Abstract: We present a computational investigation of binding affinity of different types of drugs with chitin nanocarriers. Understanding the chitn polymer-drug interaction is important to design and optimize the chitin based drug delivery systems. The binding affinity of three different types of anti-bacterial drugs Ethionamide (ETA) Methacycline (MET) and Rifampicin (RIF) with amorphous chitin nanoparticles (AC-NPs) were studied by integrating computational and experimental techniques. The binding energies (BE) of hydrophobic ETA, hydrophilic MET and hydrophobic RIF were −7.3 kcal/mol, −5.1 kcal/mol and −8.1 kcal/mol respectively, with respect to AC-NPs, using molecular docking studies. This theoretical result was in good correlation with the experimental studies of AC-drug loading and drug entrapment efficiencies of MET (3.5 ± 0.1 and 25± 2%), ETA (5.6 ± 0.02 and 45 ± 4%) and RIF (8.9 ± 0.20 and 53 ± 5%) drugs respectively. Stability studies of the drug encapsulated nanoparticles showed stable values of size, zeta and polydispersity index at 6 °C temperature. The correlation between computational BE and experimental drug entrapment efficiencies of RIF, ETA and MET drugs with four AC-NPs strands were 0.999 respectively, while that of the drug loading efficiencies were 0.854 respectively. Further, the molecular docking results predict the atomic level details derived from the electrostatic, hydrogen bonding and hydrophobic interactions of the drug and nanoparticle for its encapsulation and loading in the chitin-based host-guest nanosystems. The present results thus revealed the drug loading and drug delivery insights and has the potential of reducing the time and cost of processing new antibiotic drug delivery nanosystem optimization, development and discovery.